Habilidades sociales y riesgo de embarazo en adolescentes de la institución educativa Nuestra Señora de Guadalupe - Alfaro Albitres, Sarita Elizabeth (2020)
The present quantitative research study with a descriptive approach, was carried out in the city of Guadalupe, aims to establish the relationship between social skills and risk of pregnancy in adolescents of the educational institution Our Lady of Guadalupe, the data obtained were presented in tables single and double entry statistics, the sample studied was made up of 145 adolescents between 1st and 5th year and the statistical analysis was performed using the spearman brown test, reaching the following conclusions; in social skills, in the assertiveness dimension, 51.7% have high social skills; in communication, 58.6%; in self-esteem 52.4% and in decision-making 40.7%. Regarding the risk of pregnancy in adolescents, 62.1% of adolescents have a low risk of pregnancy, followed by 25.5% of their risk of pregnancy is high and finally 12.4% of their risk of pregnancy is risk free. There is a non-significant relationship between the assertiveness dimension and the risk of pregnancy of -0.263 with probability (p≤0.05) being highly significant, however it is shown that there is no relationship between the other social skills, the dimensions of communication, self-esteem and taking decisions with the risk of pregnancy with probabilities greater than 0.05 being not significant.